Changes in Emergency Department Geriatric Services in Quebec and Correlates of These Changes. Issue 7 (6th March 2017) - McCusker, Jane; Vadeboncoeur, Alain; Cossette, Sylvie; Veillette, Nathalie; Ducharme, Francine; Minh Vu, Thien Tuong; Ciampi, Antonio; Cetin‐Sahin, Deniz; Belzile, Eric
Abstract : Background/Objectives: To describe changes in geriatric emergency department (ED) services from 2006 (T1) to 2013/14 (T2), associated factors, and outcomes. Design: Two‐wave survey design. Setting: Province of Quebec, Canada. Participants: Lead nurses and physicians at 57 EDs that participated in both the T1 and T2 surveys. Intervention: Changes over time in ED geriatric services, observed naturalistically. Measurements: Survey questionnaires assessed: ED geriatric services (11 items) and nursing and geriatric staffing resources. Key administrative data indicators for ED bed visits for T1 and T2 for ages 75 and over included: volume of ED visits; length of ED stay; admission rate; and 30‐day return visits. Results: There was a significant overall increase in the number ED geriatric services, from mean 2.8 (SD 2.2) at T1 to mean 6.0 (SD 2.0) at T2. EDs were clustered into 3 groups based on their T1 and T2 geriatric service scores: "early adopters" (n = 12); "late adopters" (n = 27); "non‐adopters" (n = 18). Group membership was associated with three T1 variables: availability of a geriatric nurse clinician, a lower ratio of nurses to ED beds, and longer ED stays. There were significant overall increases between T1 and T2 in number of ED bed visits and ED length of stay among those aged 75 and over, decreases in hospitalization rates, but no change in ED return visits. There were no differential changes in the key indicators among the three ED clusters. Conclusions: Overall, ED geriatric services improved in Quebec from 2006 to 2013/14. EDs with a geriatric nurse clinician, relatively fewer nursing resources, and longer ED stays improved more quickly.